Go Get Data (GGD) is a framework that facilitates reproducible access to genomic data - Michael J. Cormier (Nature Portfolio, 2021)
Modern biological research is complicated by the difficulty of collecting, transforming, annotating, and integrating datasets. Here, the authors present Go Get Data, a fast, reproducible approach to installing standardized data recipes, with an application to genomics data.